(untitled) (Development Service Industry Management, 2024)
The objective of this study is to analyse academic publications on the use of cryptocurrencies for the legalization of funds obtained illegally through a bibliometric approach and to identify key trends in scientific discourse, including the most important authors, sources, themes, and countries actively researching this issue. The research methodology involves conducting a bibliometric analysis using the Scopus database and Biblioshiny software to identify the main trends in scientific publications, leading authors, journals, and key topics. The results show a sharp increase in the number of studies on this topic since 2016, indicating increased interest from the academic community in financial crimes associated with cryptocurrencies. The largest number of publications is found in journals such as the Journal of Money Laundering Control and Journal of Financial Crime. The average number of citations per article is 10.95, reflecting significant interest in the topic. At the same time, the most cited works focus on the anonymity of cryptocurrencies, regulatory challenges, and technological innovations in detecting suspicious transactions. Around 17% of the documents involve international co-authorship, highlighting the need for global efforts to address financial crimes through cryptocurrencies. This study is the first to summarize the scientific discourse on money laundering through cryptocurrencies based on a large number of publications. It identifies key themes, authors, and sources that dominate the field and tracks how research has evolved over time. The results of the study can be used to improve regulatory and legal mechanisms aimed at combating financial crimes, particularly money laundering through cryptocurrency networks.